2020
DOI: 10.3389/fphar.2020.00392
|View full text |Cite
|
Sign up to set email alerts
|

Bazedoxifene Attenuates Abdominal Aortic Aneurysm Formation via Downregulation of Interleukin-6/Glycoprotein 130/Signal Transducer and Activator of Transcription 3 Signaling Pathway in Apolipoprotein E–Knockout Mice

Abstract: Abdominal aortic aneurysm (AAA) is a chronic inflammatory disease characterized by aortic dilatation and predominantly affects an elderly population. Accumulating evidence suggests that Interleukin-6 (IL-6) and the signal transducer and activator of transcription 3 (STAT3) play an important role in formation of AAAs. However, it remains unclear whether Bazedoxifene (BAZ) could suppress the activation of IL-6/GP130/STAT3 in vascular cells and the formation of AAA. Here we explored the effect of BAZ on AngII-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Using multiple ligand simultaneous docking (MLSD) and drug repositioning, Li et al showed bazedoxifene and raloxifene, which are approved agents for osteoporosis in post-menopausal women with high risk of breast cancer, could inhibit IL-6/glycoprotein 130 interaction resulting in inhibited IL-6 signaling [ 123 ]. These two drugs are found to inhibit IL-6 signaling in tumor and cardiovascular disease including aortic aneurysm [ [124] , [125] , [126] , [127] ], which may also effect in other inflammatory settings. In a randomized, double-blind trial conducted by Ridker PM et al, antiinflammatory treatment by anti-IL-1β antibody canakinumab decreased the rate of recurrent cardiovascular events than placebo [ 128 ].…”
Section: Promising Strategies For Hypercoagulability In Covid-19mentioning
confidence: 99%
“…Using multiple ligand simultaneous docking (MLSD) and drug repositioning, Li et al showed bazedoxifene and raloxifene, which are approved agents for osteoporosis in post-menopausal women with high risk of breast cancer, could inhibit IL-6/glycoprotein 130 interaction resulting in inhibited IL-6 signaling [ 123 ]. These two drugs are found to inhibit IL-6 signaling in tumor and cardiovascular disease including aortic aneurysm [ [124] , [125] , [126] , [127] ], which may also effect in other inflammatory settings. In a randomized, double-blind trial conducted by Ridker PM et al, antiinflammatory treatment by anti-IL-1β antibody canakinumab decreased the rate of recurrent cardiovascular events than placebo [ 128 ].…”
Section: Promising Strategies For Hypercoagulability In Covid-19mentioning
confidence: 99%
“…In some inflammatory cardiovascular diseases, expression of IL-6 is dependent on STAT3. Inhibition of STAT3 activation results in reducing the expression of IL-6 in myocardium or blood vessels ( Shi et al, 2020 ; Yan et al, 2020 ). In autoimmune disease, dendritic cells play an indisputable role in instructing the polarization of CD4 + Th17 cells in immune response through generation of cytokines such as IL-6, IL-23, and IL-1β ( Coutant and Miossec, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these infiltrating cells also secrete various inflammatory cytokines, such as IL-1β [34], IL-6 [35], and TNF-α [36], which further drive inflammatory responses and ultimately lead to AAA rupture. Studies have suggested that reducing the activation of these proinflammatory cytokines could inhibit the formation and progression of AAA [34][35][36][37]. Thus, it is clear that therapeutic drugs targeting the inflammatory response can be very effective in improving AAA.…”
Section: Discussionmentioning
confidence: 99%